Intervening on burnout in complex organizations -the incomplete process of an Action Research in the hospital - Ramos, S.; Costa, P.; Passos, A. M.; Silva, S. A.; Leite, E. S. (Frontiers in Psychology, 2020)
Health professionals are at high risk for developing burnout symptoms. Directed at reducing the organizational variables affecting professionals’ burnout, an action research was developed in a specific sector of a large hospital, with 59 doctors, 66 nurses, and 42 ancilliary professionals. Researchers conducted 11 interviews, one focus group, and 20 h of in loco observation. Professionals report demotivation and the need to address the emotional part of their job. Nonetheless, the hierarchy blocked the proposed intervention possibilities. Organizational factors are unequivocally relevant, particularly in complex settings with emotionally charged interactions, and the direct hierarchy is pivotal for facilitating organizational change.